Washington Street, ca. 1855-65 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking south of the left side of Washington Street between School and Milk Streets. The multi-story buildings display business signage. On the right side of the image is the Old South Meeting House. 10 1/8 x 7 1/4 overall 12 x 10 Photographs